Efektivitas Model Project-Based Learning Terintegrasi STEM Dalam Peningkatan Kemampuan Literasi Sains - Zendrato, Eliasman Kristian; Gea, Hendri Anugrah; Telaumbanua, Grace Cristin; Gea, Fitri Kurniati; Halawa, Elvian Kardiani; Hulu, Erlan Ndika; Telaumbaua, Hartati; Gulo, Fitri Nurhayati; Harefa, Edward (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study was to determine the effectiveness of the integrated project based learning (PjBL) model of science, technology, engineering, and mathematics (STEM) in improving students' reading skills. This research method is a quantitative research method. In this study, a survey of survey materials was conducted and analyzed with instrument tests, pretests, and hypothesis tests. This study involved two groups, namely the experimental group and the control group using the STEM integrated PJBL model. The results showed that the application of this learning model showed significant results in improving students' scientific literacy. The test used quantitative research methods, namely. instrumental analysis test, hypothesis test and N-Gain test, so that the information obtained can be trusted in answering research questions. The results of the analysis showed that students who took part in project-based learning with a STEM approach had better understanding, and scientific literacy compared to traditional learning.